Long non-coding RNA LINC00467 regulates hepatocellular carcinoma progression by modulating miR-9-5p/PPARA expression. Issue 9 (4th September 2019) - Cai, Kerui; Li, Tieling; Guo, Ling; Guo, Haifeng; Zhu, Wei; Yan, Lei; Li, Fujuan
Abstract : Abstract : The aim of this study was to analyse the expression pattern and elucidate the mechanistic involvement of long non-coding RNA LINC00467 in hepatocellular carcinoma (HCC). The relative expression of LINC00467 and microRNA (miR)-9-5p was determined by real-time polymerase chain reaction. Cell viability was measured using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. The cell proliferation was analysed by cell counting. Cell migration and invasion were monitored by Transwell assay. The luciferase reporter assay was employed to investigate the regulatory effect of miR-9-5p on LINC00467 and peroxisome proliferator-activated receptor alpha (PPARA). The endogenous PPARA protein was quantified by western blotting. It was found that LINC00467 was aberrantly decreased in HCC. The ectopic expression of LINC00467 significantly suppressed cell viability, proliferation, migration and invasion. LINC00467 functioned as a sponge for miR-9-5a and negatively regulated miR-9-5p expression. We also identified PPARA as the direct target of miR-9-5p. siRNA-mediated knockdown of PPARA in LINC00467-proficient cells promoted cell viability, migration and invasion. Our data indicate the critical involvement of LINC00467/miR-9-5p/PPARA signalling in the incidence and progression of HCC.